Determinants of Pharmaceuticals Companies' Capital Structures Listed on the Indonesian Stock Exchange - Silvana Syah; Adler Haymans Manurung; Agung Dharmawan Buchdadi; I Gusti Ketut Agung Ulupui; Gatot Nazir Ahmad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Capital structure is a complex financial decision because it is related to other financial decision variables. This study aims to determine what factors affect the capital structure of pharmaceutical companies listed on the IDX in 2016-2021. The population in this research is all pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) from 2016-to 2021. The sample was selected using the purposive sampling method and obtained a sample of 10 pharmaceutical companies. The data source is secondary data from the website (www.IDX.co.id). This study uses panel regression analysis. Company Growth, Tangibility, and Firm Size are three variables that have a significant effect on capital structure. Liquidity, NDTS and profitability had no effect on capital structure. As a result, this variable does not need to be used as a proxy for investment considerations, particularly in the pharmaceutical sector.